Incidence Trends and Survival Prediction of Malignant Skin Cancer: A SEER-Based Study - Zhu S; Sun C; Zhang L; Du X; Tan X; Peng S (International Journal of General Medicine, 2022)
Sirong Zhu,1,* Chao Sun,1,* Longjiang Zhang,1 Xiaoan Du,1 Xiaodong Tan,1,2 Shuzhen Peng3 1School of Public Health, Wuhan University, Wuhan, Hubei, People’s Republic of China; 2School of Nursing, Wuchang University of Technology, Wuhan, Hubei, People’s Republic of China; 3The People’s Hospital of Huangpi, Wuhan, Hubei, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiaodong Tan; Shuzhen Peng, Email 00300469@whu.edu.cn; 1718274898@qq.comPurpose: This study aimed to analyze the incidence trend and further explore the risk factors influencing the survival among patients of malignant skin cancer in America.Methods: Age-adjusted incidence rates, annual percentage change (APC) of different sex and ethnicity in 1973– 2015 and patient records were extracted from the Surveillance, Epidemiology, and End Results (SEER) database. Univariate analysis and multivariate Cox regression were used to analyze risk factors influencing the survival in skin cancer patients. Survival curves and nomograms were constructed to evaluate the survival prediction by R.Results: The overall age-adjusted incidence of skin cancer increased in America from 1973 to 2005 (APC = 2.8%, 95% CI: 2.6– 2.9%, P < 0.05), particularly in white patients, 66-year-old people, and males. The 3- and 5-year overall survival (OS) rates were 51.4% and 33.8%, respectively. Independent predictors for short OS include age over 65, white ethnicity, other marital status and no surgery (P < 0.05). Stage was not an independent factor of survival (P > 0.05). The nomogram with a C-index of 0.72 (95% CI: 0.71– 0.73) matched an appropriate calibration curve.Conclusion: Incidence of skin cancer in America was on the rise during 1973– 2015 based on SEER database. Age, ethnicity, marital status and surgical history were related with survival of malignant skin cancer. Nomograms were effective tools for predicting the survival prognosis.Keywords: malignant skin cancer, primary site surgery, SEER, incidence, overall survival, nomogram